Principles of economics - Case, Karl E., 1946-2016 (Pearson, 2025)
All-time bestselling Principles of Economics is trusted for its clear, thorough and complete coverage of how market economies function. Covering both macro- and microeconomics perspectives, it balances economic theory, institutional material and real-world examples, with emphasis on the art and science of economic thinking. The 14th Edition features streamlined chapters, revised problems and all-new macro data through 2023. It adds 23 new Economics in Practice boxes with recent research and analysis, such as the impact of the COVID-19 pandemic on supply chains. In MyLab, new Economics in Practice videos featuring Emily Oster make economics relevant and relatable, while equipping you for success.